Millennials Behaviour towards Digital Waqf Innovation - Wadi, Dudun Anugerah; Nurzaman, Mohamad Soleh (Universitas Muhammadiyah Yogyakarta, 2020)
High growth of internet and smartphone users has resulted in the emergence of various digital start-up companies. Those innovation has changed people’s habit, one of which is the online donation habit. However, waqf as a form of Islamic endowment has not been much in demand by the public. Today’s existing digital waqf platform has not succeeded in cultivating waqf in communities, specifically for Millennials which will dominate 70% Indonesia’s workforce in 2020-2030. This research aims to find Millennials determinants of waqf technology adoption using modified UTAUT2 model. To build respondent perception of waqf and innovation proposed, a short video was used since its rise as marketing tool. This research also examines video marketing effectiveness using EPIC model. Result from data analysis using PLS SEM model shows that Performance Expectancy, Effort Expectancy, and Social Influence are major determinants toward waqf technology acceptance. Video marketing is also found to be very effective as a marketing tool for digital waqf.